Effect of free ammonia shock on Chlorella sp. in wastewater: Concentration-dependent activity response and enhanced settleability. (1st November 2022) - Chen, Zhipeng; Qiu, Shuang; Li, Mengting; Xu, Shiling; Ge, Shijian
Highlights: Response of microalgal activities towards FA shock was concentration-dependent. Microalgal SE was improved by 12.8-fold in response to FA shock. PN was the potential dominant contributor to the enhanced microalgal SE. Increased protein and reduced lipid and carbohydrates storage ensured PN secretion. FA shock reduced biomass nutritional value but slightly affected biodiesel quality. Abstract: The unstable microbial activity and unsatisfactory settling performance impede the development and implementation of microalgal wastewater treatment, especially in high-ammonium wastewater in the presence of free ammonia (FA). The shock of FA due to the nutrient fluctuation in wastewater was demonstrated as the primary stress factor suppressing microalgal activities. Recent study has clearly revealed the inhibition mechanism of FA at a specific high level (110.97 mg/L) by inhibiting the genetic information processing, photosynthesis, and nutrient metabolism. However, the effects of various FA shock concentrations on microalgal activities and settling performance remain unknown, limiting the wastewater bioremediation efficiencies improvement and the process development. Herein, a concentration-dependent shock FA (that was employed on microalgae during their exponential growth stages) effect on microalgal growth and photosynthesis was observed. Results showed that the studied five FA shock concentrations ranging from 25 to 125 mg/L significantly inhibited biomass production by 14.7–57.0%, but sharp reductions in photosynthesis with the 36.0–49.0% decreased Fv/Fm values were only observed when FA concentration was above 75.0 mg/L. On the other hand, FA shock enhanced microalgal settling efficiency by 12.8-fold, which was believed to be due to the stimulated intra- and extracellular protein contents and thereby the enhanced extracellular polymer substances (EPS) secretion. Specifically, FA shock induced 40.2 ± 2.3% higher cellular protein content at the cost of the decreased carbohydrates (22.6 ± 1.3%) and fatty acid (39.0 ± 0.8%) contents, further improving the protein secretion by 1.21-fold and the EPS production by 40.2 ± 2.3%. These FA shock-induced variations in intra- and extracellular biomolecules were supported by the up-regulated protein processing and export at the assistance of excessive energy generated from fatty acid degradation and carbohydrates consumption. In addition, FA shock significantly decreased the biomass nutritional value as indicated by the 1.86-fold lower essential amino acid score and nearly 50% reduced essential to non-essential amino acids ratio, while slightly decreased the biodiesel quality. This study is expected to enrich the knowledge of microalgal activities and settling performance in response to fluctuant ammonium concentrations in wastewater and to promote the development of microalgal wastewater treatment. Graphical abstract: Image, graphical abstract